Efeitos dos treinamentos funcional e tradicional sobre a aptidão física e qualidade de movimento de idosas sedentárias - Resende Neto, Antonio Gomes de (2017)
Introduction: Traditional strength training protocols, despite its proven morphological and neuromuscular benefits, have been questioned about its effects on performance improvement for daily life activities in the elderly, and functional training (TF) may be a better strategy for this purpose. However, there is a lack of research comparing and integrating TF with traditional training methods to better observe the real effects on multisystem adaptive responses. Objective: Analyze comparatively the effects of 12 weeks of functional training and traditional training in physical fitness and quality of movement in sedentary elderly women. Metodology: This is a random clinic essay with the participation of 25 old women divided in two distinct groups: Functional Training (TF: n=13; 64,8 ± 4,6 years; 29,6 ± 5,2 kg/m-²) and Traditional Training (TT: n=12; 66,0 ± 5,5 years; 28,5 ± 5,6 kg/m-²). Senior Fitness Test was used to stablish physical fitness and a dinamometric lumbar complementary test to determine maximal isometric strenght. To evaluate quality of movement it was used the Functional Movement Screen (FMS). Datas were analyzed through ANOVA 2x3 and Sidak post-hoc. Results: Past to 8 weeks, when compared to TT, TF group has promoted statistic and significant improvements in: balance/agility (p=0,03; +7%), lower limb strenght (p=0,03; +18%), upper limb strenght (p = 0,02; +15%), cardiorespiratory capacity (p = 0,02; +8%) and isometric strenght (p = 0,04; +16%). In 12 weeks, TF has presented significative diferences in: balance/agility (p = 0,00; +9%), lower limbs strenght (p = 0,03; +18%), cardiorespiratory capacity (p = 0,01; +7%) and quality of movement (p = 0,02; +16%), when compared to TT. However, flexibility test has not shown differences between groups. And the two groups improved significantly in all variables (p≤0,05) in relation to the initial values. Conclusion: Although both training protocols prove to be efficient in improving physical fitness and movement quality in sedentary elderly women, applied functional training is more effective than traditional training.